LA DOCTRINA DEL HALLAZGO CASUAL DURANTE LAS ACTUACIONES DE INSPECCIÓN: UN COMENTARIO A LA RECIENTE JURISPRUDENCIA DEL TRIBUNAL SUPREMO ESPAÑOL - Tirado Barrera, José Antonio (Revista de Derecho, 2020)
This paper analyzes the recent jurisprudence of the Spanish Supreme Court on casual findings during the development of administrative inspections. With regard to a decision of the Comisión Nacional de los Mercados y la Competencia, wich validated the finding of incriminating evidence that was not covered by the respective inspection order, the conditions that must be met for the application of the doctrine are discussed of the casual finding, the same that has been recognized by spanish and european jurisprudence.